2021
DOI: 10.1002/ldr.4019
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate stability and organic carbon stock under different land uses integrally regulated by binding agents and chemical properties in saline‐sodic soils

Abstract: Aggregate stability and soil organic carbon (SOC) are critical for maintaining soil structure and preserving soil productivity. Land use substantially affects the process of soil aggregate stabilization and SOC sequestration, yet the detailed mechanisms have not been well studied in degraded soil ecosystems (e.g., saline-sodic soils).Therefore, to interpret the effects of land-use changes on soil aggregate stability and SOC stocks in saline-sodic soils, soils were sampled from four major land-use areas (degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
3
10
0
Order By: Relevance
“…The oxalate-extractable Fe/Al oxides can improve soil aggregate stability by forming complexes with clay under saline-sodic soil (Feng et al, 2021). The relatively high clay content in our study seems to support this view.…”
Section: Linkages Between Soc Stocks and The Mass Proportions And Sta...supporting
confidence: 76%
See 3 more Smart Citations
“…The oxalate-extractable Fe/Al oxides can improve soil aggregate stability by forming complexes with clay under saline-sodic soil (Feng et al, 2021). The relatively high clay content in our study seems to support this view.…”
Section: Linkages Between Soc Stocks and The Mass Proportions And Sta...supporting
confidence: 76%
“…This may the cementation of inorganic components (crystalline Fe/Al oxides) plays a more vital role in soil aggregate stability than soil organic matter (Torres‐Sallan et al, 2018). The oxalate‐extractable Fe/Al oxides can improve soil aggregate stability by forming complexes with clay under saline‐sodic soil (Feng et al, 2021). The relatively high clay content in our study seems to support this view.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results showed that certain exchangeable polyvalent cations (e.g., Mg 2+ , Ca 2+ ) was positively related to WMD and proportions of macro‐aggregates, particularly small macro‐aggregates (Figure 8a). It has been reported that exchangeable Ca 2+ and Mg 2+ and was positively related to WMD in chernozem and saline‐sodic soils (Feng et al, 2021; Yao et al, 2022). Higher Ca 2+ content generally results in greater aggregate stability owing to the bridging of Ca 2+ , which forms clay‐polyvalent and metal–organic matter complexes (Chen et al, 2019; Rowley et al, 2017).…”
Section: Discussionmentioning
confidence: 98%